Coding Parking Functions by Pairs of Permutations - Burman, Yurii; Shapiro, Michael (The Electronic Journal of Combinatorics, 2003)
We introduce a new class of admissible pairs of triangular sequences and prove a bijection between the set of admissible pairs of triangular sequences of length $n$ and the set of parking functions of length $n$. For all $u$ and $v=0,1,2,3$ and all $n\le 7$ we describe in terms of admissible pairs the dimensions of the bi-graded components $h_{u,v}$ of diagonal harmonics ${\Bbb{C}}[x_1,\dots,x_n;y_1,\dots,y_n]/S_n$, i.e., polynomials in two groups of $n$ variables modulo the diagonal action of symmetric group $S_n$.